2010
DOI: 10.1002/btpr.385
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for developing design spaces for viral clearance by anion exchange chromatography during monoclonal antibody production

Abstract: The quality-by-design (QbD) regulatory initiative promotes the development of process design spaces describing the multidimensional effects and interactions of process variables on critical quality attributes of therapeutic products. However, because of the complex nature of production processes, strategies must be devised to provide for design space development with reasonable allocation of resources while maintaining highly dependable results. Here, we discuss strategies for the determination of design space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Because most mAbs feature basic isoelectric points (pIs), AEX chromatography can be operated near neutral pH to bind acidic host cell protein (HCP), virus, DNA, and leached protein A impurities, while allowing the positively charged mAb to flow through unbound . Typical mAb loadings for AEX polishing resins are between 50 and 200 g mAb/L resin, which allow for acceptable impurity clearance with >95% yield …”
Section: Introductionmentioning
confidence: 99%
“…Because most mAbs feature basic isoelectric points (pIs), AEX chromatography can be operated near neutral pH to bind acidic host cell protein (HCP), virus, DNA, and leached protein A impurities, while allowing the positively charged mAb to flow through unbound . Typical mAb loadings for AEX polishing resins are between 50 and 200 g mAb/L resin, which allow for acceptable impurity clearance with >95% yield …”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophages, endogenous CHO Type C retrovirus‐like particles (RVLPs), and biologic feedstreams have been used in attempts to economically predict the outcomes of viral clearance studies . However, due to the differences in physicochemical characteristics of bacteriophage models and the complexities involved in producing purified and highly concentrated RVLP spiking stocks, the scope of utility for these surrogates have remained narrow.…”
Section: Introductionmentioning
confidence: 99%
“…The operational range for conductivity and pH was based on conditions for which effective viral clearance was measured (assumed to be over 4 log 10 for the Xenotropic Murine Leukemia Virus), based on in‐house information. Several published studies have demonstrated robust viral clearance on various AEX chromatography media under comparable pH and conductivity ranges studied in this article …”
Section: Introductionmentioning
confidence: 86%